Determinants of official development assistance in the post-cold war period - HE, Fan (Institutional Knowledge at Singapore Management University, 2008)
Using the data of 21 member countries of Development Assistance Committee of OECD from 1990 to 2005, we empirically examine the effects of different factors that determine the level of a country’s relative ODA (official development assistance as a proportion of GNI ). We find that a country's relative ODA is positively related to its economic position, public social expenditure as a proportion of GDP, and level of economic openness, and negatively related to the level of GDP per capita and fiscal revenue. This means that a country’s expenditure on foreign assistance increases as it becomes more prominent within the global economy, and as the country’s electorate becomes more concerned with the objectives of welfare policies. Wealthy countries, however, are not necessarily more predisposed towards philanthropy than poor countries, and countries with large fiscal revenues are not likely to provide more assistance than thoes with less fiscal income. Thus, we find empirical support for both the realist theory of international politics and those based on domestic political factors.